Impasses na aprendizagem e inclusão escolar: estudos de caso sob a ótica da Psicanálise - Luciana Renata Moreira Fonseca (2015)
This dissertation refers to a psychoanalytic intervention research focused on barriers in learning. It presents the results of an investigation into the possible phenomena that affect the teaching-learning process and can contribute to produce impasses in such a process. For this purpose, it was sought to know the strategies that the selected school for the study uses to intervene with the public that does not learn at the right age. It was also made a study of case with two children of that institution, who proved to be refractory to these proposals. Using the conversation, the study of the case and the clinical and pedagogical diagnosis, it was possible to recover the school history of these students, identify if their barriers to learning were from conceptual and pedagogical order or subjective and intervene to assist them in overcoming their difficulties. The interventions helped in the learning process with the students about the relationship between their impasses and its subjectivity. The hypothesis raised is that when the pedagogical practices used with students who have impairments in learning fail is because there is something of their singularity that must be taken into account for the student to continue in their studies.